Recurrent reactive infectious mucocutaneous eruption (RIME) in two adolescents triggered by several distinct pathogens including SARS‐CoV‐2 and influenza A. Issue 5 (13th September 2021) - Song, Amy; Nicholson, Cynthia; Maguiness, Sheilagh
Abstract: Reactive infectious mucocutaneous eruption (RIME) was proposed as new terminology to encompass postinfectious mucocutaneous eruptions. The term includes all postinfectious mucocutaneous eruptions such as the widely reported Mycoplasma pneumoniae ‐induced rash and mucositis (MIRM). Very few reports in the literature regarding recurrent RIME are found. We present two adolescent cases of recurrent RIME that involve SARS‐CoV‐2 and influenza A where the latter is a newly reported infectious trigger; in both patients, the initial episode was likely triggered by Mycoplasma pneumoniae (MP) infection.